The Real Exchange Rate : Assessment and Trade Impact in the Context of Fiji and Samoa - Gottschalk, Jan (IMF Working Papers; Working Paper ;, 2016)
This paper provides an assessment of real exchange rate measures and their impact on trade performance with special reference to two Pacific island countries, Fiji and Samoa. The analysis shows that the commonly used CPI-based real effective exchange rate (REER) measure provides a useful starting point of assessment, but alternative measures based on other price and cost indices should be used to check the robustness of the results, particularly given the large impact of global commodity prices on small open economies. The paper also offers some illustrations of how to quantify the impact of exchange rate movements on trade, especially in the face of data constraints in small open economies.